Assessing the Health Status of Loharpatti Municipality, Madhesh Province, Nepal: A Community Health Diagnosis Need Assessment Survey (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The health status of a country depends on the socio-economic status of the country’s people, their level of education, access to health services and so on. Therefore, this study aims to define existing problems in the community, identification of local resources (manpower, money, and material) of the community, identification of the basic health needs and problems of the community, set priorities of health needs for community health action, implementing and evaluating health action by and for the community.MATERIALS AND METHODS: We, the students of the 15th Batch of the MBBS program at Janaki Medical College (Tribhuvan University) did a comprehensive Community Health Diagnosis (CHD) from 16th February 2021 to 25th March 2021 in Loharpatti Municipality, Ward No-03 of Mahottari District. Primary and secondary data were collected for the study. Two hundred forty six households and their members were selected by simple random sampling method.RESULTS: About 90% of participants went to health centres and health post for the treatment during illness. Our observation showed that 82% of households maintained appropriate environmental cleanliness around the house. About 74% of the remaining 26% used temporary methods and the most commonly used method was IUD by females. By analyzing the finding and discussing with the community leaders and the people real needs were identified and prioritized based on available resources. The prioritized needs were: KAP on child marriage and dowry system.CONCLUSIONS: Loharpatti municipality was a rural settlement with low education status and had little idea about the consequences of early child marriage. The practice of child marriage has historical roots in the municipality. Therefore, prioritizing economic empowerment programs can help reduce socioeconomic constraints; conversely, working with religious and community leaders is essential to promoting change and encouraging discourse.